Motivasi dan Tantangan Tamatan Perawat Dalam Mencapai Kelulusan NCLEX-RN di California - Sitorus, Evie Siregar; Tambunan, Evelyn Hemme (Fakultas Ilmu Keperawatan Universitas Klabat, 2024)
Introduction: Significant factors in influencing students' ability to pass the competency test include academic, cognitive, and individual aspects. Several factors that influence the success of the competency test from the perspective of student preparation in learning include motivation, reading ability, record management, time management, and critical thinking skills. Objective: This study aims to analyze the motivation and challenges of nurse graduates from Universitas Advent Indonesia in achieving graduation on the NCLEX-RN exam in California. Method: This study is a qualitative study with a phenomenological study that collects research data through in-depth interviews consisting of six UNAI alumni participants in California. Results: the results of the study in the form of research themes, namely: preparing for and requirements for the NCLEX exam, factors causing failure to pass the NCLEX exam, and motivation to take and pass the NCLEX exam. Conclusion: Nurses’ motivations in achieving NCLEX RN graduation in California are to improve finances, flexible working hours, make family happy, and be involved in complex patient care. Nurses’ challenges in achieving NCLEX RN graduation in California are meeting the administrative requirements for registering for the NCLEX RN exam, managing study time, understanding the material and the purpose of the exam questions, and adapting to the CAT exam system